The Age of Initiation of Drug Use and Sexual Behavior May Influence Subsequent HIV Risk Behavior: A Systematic Review. (7th December 2013) - Baldwin, Patrick; Shrestha, Roman; Potrepka, Jessica; Copenhaver, Michael
Abstract : Researchers examining injection drug users (IDUs) in drug treatment have been trying for decades to determine the optimal way to intervene to prevent the transmission and spread of human immunodeficiency virus (HIV) in this population. Although efficacious HIV risk reduction interventions are widely available, questions remain about what specific factors are most related to HIV risk behavior and defined as unprotected sexual activity and/or high risk drug use. This review involved an evaluation of the research literature in order to better understand the association between drug use and sexual behavior debut on HIV risk behavior. Findings suggest that drug use debut and sexual behavior debut may be related to subsequent HIV risk behavior. Evidence to date implies that intervening at an earlier age to assist youth to avoid or delay these high risk behaviors may be an additional means of reducing subsequent HIV risk.